Turkish Neonatal Society guideline on neonatal infections-diagnosis and treatment - Satar, Mehmet (Turk Pediatri Ars, 2018)
Neonatal infections are a major cause of morbidity and mortality in the first month of life, especially in developing countries. Despite advances in neonatology, neonatal infections still haves clinical importance because of nonspecific signs and symptoms, no perfect diagnostic marker, and interference with non-infectious diseases of newborns. Diagnosis is typically made by clinical and laboratory findings. Empiric antibiotic therapy should be started in a newborn with signs and symptoms of infection after cultures are taken according to the time of the signs and symptoms, risk factors, admission from community or hospital, focus of infection, and antibiotic susceptibility estimation. Treatment should be continued according to clinical findings and culture results. Intrapartum antibiotic prophylaxis, proper hand washing, aseptic techniques for invasive procedures, appropriate neonatal intensive care unit design, isolation procedures, and especially breast milk use are needed to prevent infections. The use of diagnosis and treatment protocols increases clinical success.